Lapatinib Plus Local Radiation Therapy for Brain Metastases From HER-2 Positive Breast Cancer Patients and Role of Trastuzumab: A Systematic Review and Meta-Analysis - Khan, Muhammad; Zhao, Zhihong; Arooj, Sumbal; Zheng, Tao; Liao, Guixiang (Frontiers in Oncology, 2020)
Background:Intracranial activity of lapatinib has been demonstrated in several studies in patients with human epidermal growth factor receptor-2 positive breast cancers (HER-2+ BC). Stereotactic radiosurgery has been increasingly used as the local therapy for brain metastases in breast cancer patients. Increased objective response rate was observed for lapatinib plus whole brain radiotherapy is such patients with high toxicity. Objective: We seek to obtain clinical evidence of synergistic efficacy of lapatinib in combination with radiation therapy, in particular, SRS. Methods & Materials:We carried out a comprehensive research using the following databases: PubMed; Medline; EMBASE; Cochrane library. These databases were searched until 10 June 2020. PRISMA guidelines were followed step by step for carrying out this systematic review and meta-analysis. Review Manager v 5.4 software was used for statistical evaluation of data. Results:Overall 6 studies with 843 HER-2 positive breast cancer patients (442 HER-2 amplified disease, 399 luminal B disease) were included in this systematic review and meta-analysis. A total 279 patients had received lapatinib in addition to HER-2 antibody (trastuzumab) plus/minus chemoradiotherapy while 610 patients had received trastuzumab-based management or only chemoradiotherapy. Lapatinib-based management of BM was associated with significant increase in overall survival (HR 0.63 [0.52, 0.77], p<0.00001). Combination of the two (trastuzumab plus lapatinib) was associated with increased survival advantage compared to each agent alone (0.55 [0.32, 0.92], p=0.02). SRS in combination with lapatinib was associated with increased local control (HR 0.47 [0.33, 0.66], p=0.0001). Ever use of lapatinib with SRS was associated an increased survival as reported in two studies (Shireen, et al.:27.3 vs 19.5 months, p = 0.03; Kim, et al.:33.3 vs 23.6 months, p=0.009). Kim, et al. also revealed significant increase in intracranial activity with concurrent lapatinib reporting 57% complete response compared to 38% (p<0.001) as well as lower progressive disease rate of 11% vs 19% (p<0.001). Risk of radiation necrosis was decreased with lapatinib use. Conclusions:Lapatinib hasshown intracranialactivity and yielded better survival for HER2+BC patients with BMs. SRS in combination with ever use of lapatinib had better local control and were associated with better survival. Radiation necrosis risk was reduced with the use of lapatinib.